2014
DOI: 10.1371/journal.pone.0098932
|View full text |Cite|
|
Sign up to set email alerts
|

Automated Assessment of β-Cell Area and Density per Islet and Patient Using TMEM27 and BACE2 Immunofluorescence Staining in Human Pancreatic β-Cells

Abstract: In this study we aimed to establish an unbiased automatic quantification pipeline to assess islet specific features such as β-cell area and density per islet based on immunofluorescence stainings. To determine these parameters, the in vivo protein expression levels of TMEM27 and BACE2 in pancreatic islets of 32 patients with type 2 diabetes (T2D) and in 28 non-diabetic individuals (ND) were used as input for the automated pipeline. The output of the automated pipeline was first compared to a previously develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…One of the major threats to tropical biodiversity is the fragmentation process, which can cause changes in the structure, composition and functions of communities over time [ 1 ]. In plant communities, species homogenization and floristic differentiation are two possible consequences of this process [ 2 , 3 ]. Species homogenization is when sensitive species disappear locally and fragments are dominated by tolerant species [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…One of the major threats to tropical biodiversity is the fragmentation process, which can cause changes in the structure, composition and functions of communities over time [ 1 ]. In plant communities, species homogenization and floristic differentiation are two possible consequences of this process [ 2 , 3 ]. Species homogenization is when sensitive species disappear locally and fragments are dominated by tolerant species [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown flora homogenization in fragments [ 2 ], while others have indicated that this phenomenon is not always predominant, and that small fragments located in modified human landscapes can retain high levels of biodiversity [ 3 , 5 ]. A possible explanation for these different results is that, over the time, landscape composition (matrix type and forest cover) determines the changes in species of a plant assemblage in fragments that occur in human modified landscapes [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pancreatic islet can be segmented by constructing a graph to represent the high cell density. This approach has been applied to automated assessment of β-cell areas and density per islet based on immunofluorescence staining (5). However, this method is still limited by its assumption that there is only one islet in each image, and that the islet usually has high density cells (4).…”
mentioning
confidence: 99%